Analisis Yuridis Pemberhentian Anggota Direksi dengan tanpa Didahului Adanya Pembelaan Diri dalam RUPS - Darlene, Felicia (Notary Journal, 2021)
One of the sectors being developed by the Indonesian government is economic growth, which impact on increasing Limited Liability Companies. Provisions that contain procedures for managing a Limited Liability Company are regulated in Law Number 40 of 2007 concerning Limited Liability Companies (UU PT), one of which is the procedure for dismissing members of the Board of Directors. Article 105 of the Company Law stipulates that the dismissal of a member of the Board of Directors is taken after the person concerned is given the opportunity to defend himself. Furthermore, regarding legal protection for the dismissal of members of the Board of Directors who violate the provisions of the Company Law. The Law on Judicial Power regulates the absolute competence of each judiciary. With absolute competence, each judicial body has different jurisdiction to judge. The method used in this study is normative juridical. The results and conclusions of this study are that the dismissal of members of the Board of Directors without any prior self-defense in the GMS is invalid if the members of the Board of Directors object to his dismissal. Legal protection for members of the Board of Directors who are dismissed not in accordance with the provisions of the Company Law is to file a lawsuit to the District Court.Bahasa Indonesia Abstrak: Salah satu sektor yang sedang dikembangkan oleh pemerintah Indonesia adalah pertumbuhan ekonomi, yang berdampak pada meningkatnya Perseroan Terbatas. Ketentuan yang memuat tata cara pengurusan Perseroan Terbatas diatur dalam Undang-Undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas (UU PT), salah satunya adalah tata cara pemberhentian anggota Direksi. Dalam Pasal 105 UU PT diatur bahwa keputusan pemberhentian anggota Direksi diambil setelah yang bersangkutan diberi kesempatan untuk membela diri. Selanjutnya mengenai perlindungan hukum atas pemberhentian anggota Direksi yang melanggar ketentuan UU PT. Undang-Undang Kekuasaan Kehakiman mengatur mengenai kompetensi absolut setiap peradilan. Dengan adanya kompetensi absolut, maka setiap badan peradilan mempunyai yurisdiksi mengadili yang berbeda-beda. Metode yang digunakan dalam penelitian ini adalah yuridis normatif. Hasil dan kesimpulan dari penelitian ini adalah pemberhentian anggota Direksi dengan tanpa didahului adanya pembelaan diri dalam RUPS adalah tidak sah jika anggota Direksi keberatan atas pemberhentian dirinya. Perlindungan hukum bagi anggota Direksi yang diberhentikan tidak sesuai dengan ketentuan UUPT adalah mengajukan gugatan ke Pengadilan Negeri.